ANALISIS RHODAMIN B PADA LIPSTIK IMPOR YANG BEREDAR DI PASAR PAGI KOTA SAMARINDA DENGAN SPEKTROFOTOMETRI UV-VISIBLE - Ruth Gratia Dwi Pangestika; Nurillahi Febria Leswana; Adhe Septa Ryant Agus (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
Rhodamine B is commonly used as a dye for textiles (silk, wool, cotton), paint, paper, and clothing. Prolonged ingestion or exposure may irritate the respiratory tract, eyes, and skin, cause nausea and vomiting, and potentially lead to liver cancer or even cell death. This study aims to identify the presence of Rhodamine B dye in imported lipsticks sold at Pasar Pagi, Samarinda City. The research involved both qualitative and quantitative analyses. The qualitative test was conducted using Thin Layer Chromatography (TLC) with an eluent mixture of ethyl acetate : ethanol : ammonia (11:2:1), while the quantitative test employed UV-Vis spectrophotometry. The qualitative results using TLC showed that sample H had an Rf value of 0.529 cm, which closely resembled the standard Rhodamine B Rf value of 0.623 cm. The quantitative analysis revealed Rhodamine B concentrations in sample A (0.12%), sample B (0.19%), sample C (0.16%), sample F (0.20%), sample G (0.16%), sample H (0.37%), sample I (0.27%), and sample J (0.03%). The validity test indicated a linear result. The precision test showed Relative Standard Deviation (RSD) values of 1.7% for samples G, H, and I. The accuracy test yielded recovery percentages in sample G of 92% (2 ppm), 99% (4 ppm), and 86% (6 ppm); and in sample H of 88% (2 ppm), 98% (4 ppm), and 94% (6 ppm).